A‐kinase anchor protein 4 precursor (pro‐AKAP4) in human spermatozoa. (8th July 2018) - Jumeau, F.; Sigala, J.; Dossou‐Gbete, F.; Frimat, K.; Barbotin, A. L.; Buée, L.; Béhal, H.; Sergeant, N.; Mitchell, V.
Abstract: Background: A‐kinase anchor protein 4( AKAP4) and its precursor pro‐AKAP4 are two major proteins in spermatozoa of rodents and mammals. Although researchers have characterized the AKAP4 expression in various species, the protein's expression in humans has not been described in detail. Objectives: The objective of this study was to characterize human pro‐AKAP4 more precisely (notably the definition of its localization and expression levels in human spermatozoa and testes). Materials and Methods: pro‐AKAP4 protein expression levels were assessed by Western blotting. The pro‐AKAP4's localization in spermatozoa and testes was determined using immunofluorescence staining and immunogold electron microscopy. Furthermore, pro‐AKAP4 protein expression levels were assessed in a series of 77 human semen samples, and associations with semen parameters were evaluated. Results: Western blotting revealed a 100‐kDa band in human sperm protein extracts. The pro‐AKAP4 was immunolocalized in the fibrous sheath of the flagellum of ejaculated spermatozoa and in elongated spermatids in human testes. A Western blot analysis of 77 normozoospermic semen samples evidenced striking differences in pro‐AKAP4 levels from one to another sample (median [interquartile range] integrated optical density = 305 [49–1038]). No correlations were found for pro‐AKAP4 levels on one hand and semen volume, sperm concentration, sperm count, sperm motility, or sperm morphology on the other ( p  > 0.05 for all). However, pro‐AKAP4 levels were positively correlated with motility after density gradient centrifugation of the semen ( r  =   0.224, p =  0.049). Discussion: AKAP4 protein might be activated as an alternative pathway to rescue sperm motility. In human spermatozoa, pro‐AKAP4 might therefore be a 'reservoir' of mature AKAP4. Conclusion: This study generated new knowledge about pro‐AKAP4 in human semen, which may be of interest in the management of male infertility.